Evaluation of clinical and laboratory variables associated with anemia in pediatric patients on hemodialysis - Johnathan S. de Freitas; Paulo Sucasas Costa; Luciane Rezende Costa; Alessandra V. Naghettini (Elsevier, 2015)
OBJECTIVE: To identify the occurrence of anemia in pediatric patients on hemodialysis and the association between hemoglobin levels and anemia in CKD-related variables. METHODS: This was a retrospective study. Patients aged up to 18 years with chronic kidney disease undergoing hemodialysis at this service between January of 2009 and December of 2010 were selected. Clinical and laboratory data were obtained from medical records. Statistical analysis was performed with chi-squared test, Student's t-test and general estimating equations (GEE) using SPSS 20.0, assuming a significance level of 5%. RESULTS: A total of 357 medical records depicting the monthly evolution of 29 patients were analyzed. The most common etiology for chronic kidney disease was malformations of the genitourinary tract (28%). Hemoglobin showed a mean (standard deviation) value of 9.20 (1.8) g/dL, with the occurrence of anemia in 65.3% of cases. Anemia was associated with hospitalization; antibiotic use; transfusion; use of intravenous iron hydroxide; low values of creatinine, hematocrit, and albumin; and high values of ferritin, aluminum, and equilibrated Kt/V (p < 0.05). The odds ratio for anemia with the use of intravenous iron hydroxide was 0.36 (95% CI: 0.25 to 0.89), i.e., a 2.78-fold higher chance of developing anemia without the use of this medication. CONCLUSIONS: Anemia predominated in children and adolescents with chronic kidney disease; intravenous iron hydroxide use was a protective factor.